Circulating extracellular vesicles derived from tumor endothelial cells hijack the local and systemic anti-tumor immune response: Role of mTOR/G-CSF pathway - Malvina Koni; Tatiana Lopatina; Cristina Grange; Alessandro Sarcinella; Massimo Cedrino; Stefania Bruno; Fabrizio Buffolo; Saveria Femminò; Giovanni Camussi; Maria Felice Brizzi (Elsevier, 2023)
Circulating tumour-derived extracellular vesicles are supposed to contribute to the spreading of distant metastasis. In this study, we investigated the impact of circulating extracellular vesicles derived from tumour-endothelial cells (TEVs) in the expansion of the metastatic bulk. We focus on the role of immune cells in controlling this process using the 4T1 triple negative breast cancer (TNBC) syngeneic model.4T1 cells were intravenously injected and exposed to circulating TEVs from day 7. The lung, spleen, and bone marrow (BM) were recovered and analysed. We demonstrated that circulating TEVs boost lung metastasis and angiogenesis. FACS and immunohistochemically analyses revealed a significant enrichment of Ly6G+/F4/80+/CD11b+ cells and Ly6G+/F4/80-/CD11b+ in the lung and in the spleen, while Ly6G+/F4/80-/CD11b+ in the BM, indicating the occurrence of a systemic and local immune suppression. TEV immune suppressive properties were further supported by the increased expression of PD-L1, PD-1, and iNOS in the tumour mass. In addition, in vitro experiments demonstrated an increase of CD11+ cells, PD-L1+ myeloid and cancer cells, upregulation of LAG3, CTLA4 and PD-1 in T-cells, release of ROS and NOS, and impaired T-cell-mediated cytotoxic effect in co-culture of TEVs-preconditioned PBMCs and cancer cells. Granulocyte-colony stimulating factor (G-CSF) level was increased in vivo, and was involved in reshaping the immune response. Mechanistically, we also found that mTOR enriched TEVs support G-CSF release and trigger the phosphorylation of the S6 (Ser235/236) mTOR downstream target. Overall, we provided evidence that circulating TEVs enriched in mTOR supported G-CSF release thereby granting tumour immune suppression and metastasis outgrowth.